2013
DOI: 10.1016/j.whi.2012.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Association of Intimate Partner Violence with Receipt of Clinical Preventive Services in Women of Reproductive Age

Abstract: Background Women who experience intimate partner violence (IPV) have a greater risk for adverse health outcomes, suggesting the importance of preventive services in this group. Little prior research has explored how IPV exposure impacts receipt of relevant preventive services. We assess the prospective association of IPV exposure with receiving specific preventive services. Methods Women in the Central Pennsylvania Women’s Health Study’s longitudinal cohort study (conducted 2004–2007; n = 1,420) identified p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 49 publications
0
16
2
1
Order By: Relevance
“…Expanding upon these findings, a prospective longitudinal study of 1,420 women found that IPV exposure increased the odds of receiving counseling for safety and violence in the home (although the overall rate was only 20%) and screening tests for HIV/STIs; no associations were observed for IPV exposure and Pap testing, contraceptive counseling, alcohol and drug use counseling, and smoking counseling. 78 In addition, it is unknown how preventive screening behaviors may differ for abused women who are ethnic minority, impoverished, or foreign-born. What we do know is that Black and Latina women with experiences of IPV are less likely to utilize mental health services and medical attention for injuries resulting from IPV compared with White women.…”
Section: Implications For Prevention and Treatmentmentioning
confidence: 99%
“…Expanding upon these findings, a prospective longitudinal study of 1,420 women found that IPV exposure increased the odds of receiving counseling for safety and violence in the home (although the overall rate was only 20%) and screening tests for HIV/STIs; no associations were observed for IPV exposure and Pap testing, contraceptive counseling, alcohol and drug use counseling, and smoking counseling. 78 In addition, it is unknown how preventive screening behaviors may differ for abused women who are ethnic minority, impoverished, or foreign-born. What we do know is that Black and Latina women with experiences of IPV are less likely to utilize mental health services and medical attention for injuries resulting from IPV compared with White women.…”
Section: Implications For Prevention and Treatmentmentioning
confidence: 99%
“…This is likely due to the fact that Coker et al used numerous assessment instruments to identify IPV exposure and type, whereas we used a single instrument, often used in clinical practice (Coker et al 2000; Gerber et al 2005; IOM. 2010; Nelson, Bougatsos, Blazina 2012; McCall-Hosenfeld, Chuang and Weisman 2013). Like the Coker study, we found a higher prevalence of physical IPV compared to non-physical IPV.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that women experiencing IPV may in fact receive more preventive services, particularly those related to sexual health (e.g., STI/HIV testing) than those not experiencing IPV. [76][77][78] Given the relatively frequent follow-up required for PrEP, however, it is unclear as to whether these findings are applicable in this context.…”
Section: Difficulties With Covert Usementioning
confidence: 99%